Pembelajaran Berdiferensiasi Menggunakan Barang Bekas pada Materi Lingkaran untuk Meningkatkan Hasil Belajar Siswa - Fice Femmy Rompis (Jurnal Didaktika Pendidikan Dasar, 2024)
Each student has uniqueness and specialties that differentiate them from each other, including in terms of learning needs. One way to overcome the problem of diverse student characteristics in learning activities is to implement differentiated learning. This research aims to improve the mathematics learning outcomes of grade 8 students at Leilem Christian Middle School, Sonder District, with differentiated learning using used materials. This research is classroom action research carried out in two cycles. The subjects of this research were 8th grade students at Leilem Christian Middle School. Data collection was carried out using observation techniques and learning outcomes tests. Data were analyzed descriptively.The research findings indicate a progressive improvement throughout each cycle. In terms of teacher engagement during the instructional activities, the average score was 84.10% in Cycle I and 92.05% in Cycle II. Similarly, student involvement exhibited an increase, with an average score of 80.69% in Cycle I and 94.32% in Cycle II. As for the student's learning outcome test results, there was an advancement from 76.67% in Cycle I to 90% in Cycle II. In conclusion, differentiated instruction utilizing recycled materials is capable of enhancing student learning outcomes.